Retention of formaldehyde in the tissues of two tropical fish species following exposure to therapeutic levels - Subasinghe, R. P.; Yusoff, F. M. (Hindawi Limited, 1993)
Formalin is an effective fish chemotherapeutant which is used to control certain ectoparasitic and bacterial infections. It is toxic to fish and its pathological and physiological effects have been reported. An experiment was conducted to elucidate the possibility of retention of formaldehyde in the muscles of two tropical food fish species, following exposure to therapeutic levels of formalin. The results indicated that Puntius gonionotus (Bleeker), retained 5·75 ppm formaldehyde following exposure to 50 ppm formalin for 24h. In contrast, Clarias batrachus (L.) retained 14·03 ppm and 18·72 ppm formaldehyde following exposure to formalin at 50 ppm and 100 ppm for 24 h respectively. However, no formaldehyde was detected after keeping the exposed fish in clean running water for 24h.